5-Lipoxygenase Knockout Aggravated Apical Periodontitis in a Murine Model. (April 2018) - Wu, Y.; Sun, H.; Yang, B.; Liu, X.; Wang, J.
5-Lipoxygenase (5-LO) plays a vital role in the host innate immune response, including bacteria-induced inflammation. Apical periodontitis (AP) is due to immune disorders caused by imbalances between bacterial invasion and subsequent host defense response. In this work, we investigated the role of 5-lipoxygenase in AP by using 5- lo knockout mice (5- lo -/- mice). Results showed that 5- lo -/- mice had greater periapical bone loss and more osteoclasts positive for tartrate-resistant acid phosphatase staining than did wild-type mice, as determined by micro–computed tomography and histologic staining. The inflammation- and osteoclastogenesis-related factors IL-1β, TNF-α, RANK, and RANKL were also significantly elevated in 5- lo -/- mice, whereas osteoprotegerin was reduced. Furthermore, peritoneal macrophages from 5- lo -/- mice revealed an obviously impaired ability to phagocytose the AP pathogenic bacteria Fusobacterium nucleatum . In vivo experiments confirmed that 5- lo knockout led to decreased macrophage recruitment and increased F. nucleatum infection around the periapical area due to decreased leukotriene B4 and LXA4 production. All these results showed that 5- lo knockout impaired the host innate immune system to promote the release of bone resorption–related factors. Therefore, 5- lo deficiency aggravated AP in an experimental murine AP model.